Global Empirical Model of Sporadic-E Occurrence Rates - Parsch, Eli V.; Franz, Anthony L.; Dao, Eugene V.; Wu, Dong L.; Swarnalingam, Nimalan; Salinas, Cornelius C. J. H.; Emmons, Daniel J. (Frontiers in Astronomy and Space Sciences, 2024)
Intense ionization enhancements in the Earth’s ionosphere, known as sporadic-E (Es), can degrade and severely disrupt the propagation of radio signals. Although many previous studies have analyzed the characteristics and morphologies of sporadic-E, few efforts have attempted to model global Es occurrence rates (ORs) at high time resolutions. This study develops a global empirical model of blanketing sporadic-E occurrence rates using a Karhunen–Loéve Expansion (KLE) of a global OR climatology built with Global Navigation Satellite System radio occultation (GNSS-RO) and ionosonde observations. Using an fbE ≥ threshold of 3 MHz, the model outputs a blanketing sporadic-E OR for a given geomagnetic latitude, longitude, day of year, and local solar time. The model outputs are compared to digisonde observations at four sites with varying geomagnetic latitudes, resulting in correlation coefficients ranging from 0.5 to 0.9 for monthly averaged observations and an uncertainty of 11%. Furthermore, the average uncertainty is estimated to be 12%. This Global Empirical Model of Sporadic-E Occurrence Rates (GEMSOR) is capable of providing blanketing sporadic-E OR estimates for global radio frequency (RF) operations.